Theories and Concepts of Gifted Children - Nurmanzili; Salami Mahmud (TIFLUN : JURNAL PENDIDIKAN ANAK USIA DINI, 2024)
Many gifted children do not receive the educational services that are appropriate for them. By neglecting to provide them with the proper education that they should receive, will make gifted children unable to grow and develop aspects of their talent. Alferd binet proposed the concept of "Triadic model of giftedness" as an improvement model for the "Three-ring Conception of giftedness" proposed by Renzulli by adding the elements of family, school and peers (environment or neighborhood), to complement Ranzully's concept consisting of creativity, task commitment, and above-average ability. This study uses analytical descriptive qualitative research. The monk concept considers proper education for gifted children to develop their talents, such as special classes, accelerated classes or enrichment classes.